Advances in battery thermal management for electric vehicles: A comprehensive review of hybrid PCM-metal foam and immersion cooling technologies - Suresh, C.; Awasthi, Abhishek; Kumar, Binit; Im, Seong kyun; Jeon, Yongseok (Renewable and Sustainable Energy Reviews, 2025)
One of the major challenges currently facing electric vehicles (EVs) is the effective thermal management of their battery packs, which significantly impacts both battery performance and longevity. Temperature control is a critical parameter for ensuring efficient battery thermal management systems (BTMS), making the development of effective real-time heat dissipation technologies essential. Presently, most EVs utilize indirect liquid-cooling systems, which effectively reduce battery temperatures but are limited by issues such as high pumping power requirements and non-uniform temperature distribution, necessitating further research and optimization. This study examines the limitations of conventional liquid and air-cooling approaches while exploring the development potential of phase change materials (PCM) enhanced with metal foam, integrated with liquid-cooling as a promising alternative. Additionally, the current status of hybrid and immersion cooling systems is comprehensively reviewed. The effects of operational strategies and system design structures on performance and energy consumption are also evaluated. Notably, the hybrid cold plate design demonstrated a 53 % reduction in overall weight compared to the baseline design, which resulted in a 90 % decrease in power consumption. Furthermore, this study explores the impacts of BTMS on the life cycle cost, lifespan, and carbon footprint of EVs batteries. The results indicate that PCM embedded with metal foam, combined with liquid-cooling, is a highly suitable choice for fast-charging and high energy density batteries. Finally, challenges and recommendations for future research are presented to advance the field of battery thermal management systems.
Keywords: Battery thermal management system; Battery thermal managements; Economic impacts; Environment impact; Hybrid cooling; Immersion cooling; Liquid cooling; Metal foams; Phase Change; Thermal management systems; Battery thermal management system; Economic and environment impact; Hybrid cooling; Immersion cooling; Metal foam; Phase change material